Design System Monitoring Quality Air Internet Of Things Based Indoor - Damayanti, Devi Fania; Wicaksono, Ardy; Hartiyani, Selvi Dwi; Gustina, Sapriani (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2025)
Air is one of the elements that support life on Earth. Without air, humans and animals cannot breathe, and plants cannot photosynthesize. Quality air is often influenced by pollutants. Because that is, air pollution can be interpreted as the presence of foreign objects or substances in the air that change the composition of the air from normal to bad. In the research, the method used is the development method with the Research approach. And Development (R&D), method development Which used In this study, the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model was used. This study was conducted to obtain accuracy from the overall system testing. Testing on quality monitoring air use sensor MQ 135 (For air), sensor DHT 11 (for temperature and humidity sensors), OLED LCD ( hardware interface ), and ESP 8266 microcontroller have been completed. This system can be used by all parties as an air quality control system, for indoor temperature and humidity using Thingspeak.